Communication Patterns of 7th Grade Students of Sabilal Muhtadin Islamic Junior High School in Online Learning Activity - Jamiatul Hamidah; Akhmad Syakir (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2021)
This study aims to describe the communication patterns of 7th grade students at SMP Islam Sabilal Muhtadin Banjarmasin in online learning activities. The method that used in this research is qualitative descriptive method which focus on language behavior in students' social relationships. The data were obtained by transcribing the online learning activities of students of SMP Islam Sabilal Muhtadin Banjarmasin on Google Classroom. From the 12 existing classes, one class was taken as a sample with a total of 25 students. Data analysis was carried out by classifying students' communication patterns based on two categories, which are (1) the topics discussed and (2) the backgrounds of speakers and speech partners. The results show that the ethnography/communication patterns of students when in online learning activities can be identified from (1) the topics discussed and (2) the background of speakers and speech partners. Based on the topic, the communication talks about learning materials, assignments, tests/examinations, and student attendance in Google Classroom. Meanwhile, in the communication which based on the background of speakers and speech partners, conversations occur between teachers and students and between students as well. From this background, the closeness between the speaker and the speech partner in a short message shows that they understand the meaning of the message conveyed. Even though sentences are written using abbreviations and tend to be concise sentences, communication is still well established. This is shown by the coherence of each message response. Keywords: communication pattern, student, online learning Abstrak Penelitian ini bertujuan untuk mendeskripsikan pola komunikasi siswa kelas 7 di SMP Islam Sabilal Muhtadin Banjarmasin dalam kegiatan pembelajaran daring. Metode penelitian yang digunakan adalah metode deskriptif kualitatif yang memfokuskan riset pada perilaku berbahasa dalam hubungan sosial siswa. Data diperoleh dengan mentranskripsi kegiatan pembelajaran daring siswa SMP Islam Sabilal Muhtadin Banjarmasin menggunakan Google Classroom. Dari 12 kelas yang ada, diambil satu kelas sebagai sampel, dengan jumlah siswa sebanyak 25 orang. Analisis data dilakukan dengan mengklasifikasikan pola komunikasi siswa berdasarkan topik yang dibahas dan latar belakang penutur serta mitra tutur. Kesimpulan yang diperoleh dari hasil penelitian ini adalah etnografi/pola komunikasi siswa dalam kegiatan pembelajaran daring dapat diidentifikasi dari topik yang dibicarakan, latar belakang penutur, dan mitra tutur. Berdasarkan topiknya, komunikasi yang berlangsung membicarakan tentang materi pembelajaran, tugas, ulangan/ujian, dan presensi/daftar hadir siswa di Google Classroom. Sedangkan berdasarkan latar belakang penutur dan mitratutur, percakapan yang terjadi antara guru dengan siswa, serta antarsiswa. Dari latar belakang tersebut, kedekatan antara penutur dan mitra tutur dalam pesan singkat menunjukkan saling memahami makna pesan yang disampaikan. Meskipun kalimat yang ditulis menggunakan singkatan dan cenderung kalimatnya ringkas, komunikasi tetap terjalin dengan baik. Hal ini ditunjukkan dari koherensi setiap jawaban pesan. Kata Kunci: pola komunikasi, siswa, pembelajaran daring